Exosome–transmitted long non-coding RNA PTENP1 suppresses bladder cancer progression - Zheng, Rui; Du, Mulong; Wang, Xiaowei; Xu, Weidong; Liang, Jiayuan; Wang, Wenying; Lv, Qiang; Qin, Chao; Chu, Haiyan; Wang, Meilin; Yuan, Lin; Qian, Jing; et al. (Molecular cancer, 2018)
Background Extracellular communication within the tumor microenvironment plays a critical role in tumor progression. Although exosomes can package into long non-coding RNAs (lncRNAs) to mediate extracellular communication, the role of exosomal lncRNA PTENP1 in bladder cancer (BC) remains unclear. Method We detected PTENP1 expression between patients with BC and healthy controls; the expression occurred in tissues and exosomes from plasma. We assessed the diagnostic accuracy by the receiver operating characteristic curve (ROC) and the area under curve (AUC). Cell phenotypes and animal experiments were performed to determine the effect of exosomal PTENP1 . Results PTENP1 was significantly reduced in BC tissues and in exosomes from plasma of patients with BC ( P < 0.05). We found that PTENP1 was mainly wrapped by exosomes. Exosomal PTENP1 could distinguish patients with BC from healthy controls (AUC = 0.743; 95% confidence interval (CI) = 0.645–0.840). Normal cells secreted exosomal PTENP1 and transmitted it to BC cells, thus inhibiting the biological malignant behavior of BC cells by increasing cell apoptosis and reducing the ability to invade and migrate ( P < 0.05). Exosomal PTENP1 could suppress tumor growth in vivo. Furthermore, exosomal PTENP1 mediated the expression of PTEN by competitively binding to microRNA-17. Conclusion Exosomal PTENP1 is a promising novel biomarker that can be used for the clinical detection of BC. Exosomes derived from normal cells transfer PTENP1 to BC cells, which reduce the progression of BC both in vitro and in vivo and suggest that exosomal PTENP1 participates in normal-cell-to-bladder-cell communication during the carcinogenesis of BC.